Innovation and entrepreneurship in Western Canada : from family businesses to multinationals - Chrisman, James J.; Holbrook, J. Adam, 1946-; Chua, Jess H. (CEL - Canadian Publishers Collection., 2002)
A collection of articles by Canadian scholars that examines the nature of the entrepreneurial process at the national and regional levels. The book presents emerging research and scholarly perspectives on the roles of innovation, entrepreneurship, and family business in western Canadian economic development. Includes conceptual pieces, theory-building exercises based on field research, literature reviews, large-scale empirical studies, and presentations of new methodological advancements that further research in the field of business.